(untitled) (Research, Society and Development, 2019)
The present study aims to reflect on the importance of the module of notions of first aid and traffic medicine to the training of traffic instructor. For that, a descriptive and exploratory research with a qualitative approach was carried out. The participants were 12 students from a traffic instructor training course, and the data collection was done through the application of a questionnaire during the first half of 2019. The results were analyzed with approximations of the Bardin Content Analysis. The results demonstrated that the participants understood the importance of content in their academic and professional context, reflecting on the concepts worked in class and the professional ideals of the future. It was also observed that the participants have a concern with their own professional training and its impact on the work with the future drivers of vehicles and the community where they live and work. In this way, it was verified that the module of first aid and traffic medicine has importance for the training of the traffic instructor, mainly to enable it to teach future drivers of vehicles. In this way, the participants demonstrated to understand the importance of the module for their professional performance and training of the future students.